Relação entre o máximo divisor comum, o mínimo múltiplo comum e o diagrama de Venn - Santos , Paula Daniele Borges dos (2017)
The present work intends to show an illustrative approach to calculate and understand Greater Common Divisor and Least Common Multiple, seeking a greater assimilation and concretization of the learning of this content. This methodology is presented in a chromological order following the evolution of mathematical concepts. Therefore, this text, aiming to produce a meaningful approach of the subject, seeks to expose in a simple way what comes to be the Prime Numbers according to Numbers Theory and Venn Diagram according to the Set Theory, in order to visualize and obtain the Relation between Greater Common Divisor, Least Common Multiple, and Venn Diagram.